Path Analysis: Effects of Psychological and Socio-Economic Exposures During Gestational Period on the Risk of Under Nutrition in Children Under Five - Nurindahsari, Yespy Anna Wahyu; Murti, Bhisma; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2016)
Background: In Indonesia the prevalence of under nutrition in children under five in 2013 was estimated to be 12.2%. It is estimated that there are still 4.5 million children underfive with under or poor nutrition have not been detected. Poor nutrition in children under five may have serious impact on their health outcome andÃÂ  cognitive ability in later life. This study aimed to investigate the effects of psychological and socio-economic exposure during gestational period and geographical area on the risk of under nutrition in children under five.Subjects and method: This was an analytical observational using case-control design. This study was conducted in Klaten, Central Java, from 8 September to 2 December 2016. A total of 150 subjects consisting of 57 children under five with birth weight <2.500 gram and 93 children under five with birth weight Ã¢â°Â¥ 2.500 gram, were selected by fixed exposure sampling. The dependent variable was weight for age. The independent variable includedmaternal education, family income, number of children, middle upper arm circumference (MUAC), maternal gestational stress, slow fetal growth for gestasional age, low birth weight, nutritional intake, geographic area. The data were collected by a set of questionnaire, 24 hours food recall, and medical record. The data were analyzed using path analysis.Results: Nutritional intake that is lower than recommended allowance (b=3.14; 95%CI=1.09 to 5.20; p=0.003) and history of birth weight <2.500 gram (b=1.70; 95%CI=0.71 to 2.70; p=0.001) increased the risk of under nutrition in children under five. Slow fetal growth for gestational age, maternal gestational stress, family income < Rp 2,000,000, and middle upper arm circumference (MUAC), had indirect significant effect on the risk of under nutrition in children under five.Conclusion: Nutritional intake lower than recommended allowance and birth weight <2.500 gram increased the risk of under nutrition in children under five.Keywords: gestational period, psychological and socio-economic exposure, under nutrition, children under five.Correspondence:ÃÂ YespyÃÂ  Anna Wahyu Nurindahsari. School of Health Sciences Guna Bangsa, Yogyakarta.Journal of Maternal and Child Health (2016), 1(2): 83-92https://doi.org/10.26911/thejmch.2016.01.02.03